Investigating the effects of living with HIV on neural circuits involved in reward processing in adolescents - Mac Arthur, Anika (Department of Human Biology, 2025)
The CHER (Children with HIV Early Antiretroviral) trial found that early ART (12- weeks) reduced mortality and morbidity in children with perinatal HIV (CPHIV). Despite early ART, CPHIV from the CHER trial demonstrate neuroimaging alterations, but little is known about the effects of PHIV and long-term ART on the adolescent brain. Adolescence is a time of increased vulnerability to risk-taking behaviour. Here, neural circuits involved in reward processing during adolescence are investigated using functional MRI (fMRI). FMRI scans acquired during a Reward Magnitude Task were available for 106 socio economically matched adolescents (66 children perinatally infected with HIV (CPHIV), 40 controls living without HIV; age 150.4 years). Data were preprocessed using fMRIPrep. Differences in brain activation for anticipation, monetary wins vs losses, and reward/loss outcome magnitudes were compared between CPHIV and controls using FSL FEAT. Z-statistic images were thresholded at Z>3.1 and a cluster significance threshold of p=0.05. Across all subjects, there were robust responses to reward processing (win>loss) in the striatum (38,610mm3 ; peak MNI -10.1; 9.1; 0.7) and in the (ventromedial) prefrontal cortex (11,280mm3 ; peak MNI -5.3; 25.9; 41.5). There were no regions where activation increases, for any of our contrasts, were greater in CPHIV than controls, but CPHIV showed smaller activation increases than controls during anticipation and reward processing. We specifically saw smaller activation increases during processing of larger wins in 2 distinct small left superior frontal clusters as well as in the left paracingulate gyrus. Similar to findings from the Human Connectome Project in Development, the task reliably activated striatal and medial frontal regions involved in decision-making and reward seeking/processing. While we found no differences between CPHIV and controls within this reward processing network, CPHIV showed smaller activation differences in our contrasts in the left superior frontal cortex – a region involved in the working memory component of executive function. Notably, impaired working memory processing and storage, especially in the visual domain, has been reported previously in children living with HIV. The current finding suggests that HIV-related brain response abnormalities in working memory regions may impact reward processing.